Attenuation and Intensification in Exhortative Speech Acts in the Colloquial Speech of Pereira - Cisneros Estupiñán, Mireya; Serna Pinto, María Alicia (Cuadernos de Lingüística Hispánica, 2022)
This paper analyzes the strategies of attenuation and intensification in requests and commands as exhortative speech acts in Pereira’s speech. The study is synchronous (2021-2022) and qualitative. A corpus composed of 120 colloquial exhortative speech acts was formed, which were obtained by students of Technological University of Pereira through participant observation in environments both familiar and close to their social network or link network. The results indicate that in Pereira the attenuation in the commands and the requests is expressed through units that act as discursive markers, such as I say and you all will see, the use of narrations embedded between the nucleus and the mitigator of the speech act, and flattery, while the intensification is marked with exaggerations. In addition, it is evident that rhetorical questions can serve both to attenuate and intensify the illocutionary force of the exhortative act.